(untitled) (World Bulletin of Public Health, 2022)
Oral mucosal lesions are caused by irritation from malocclusion or orthodontic appliances. Wearers of orthodontic appliances some times are suffering from mucosal lesions, buccal mucosa of orthodontics patient have many pathological change such as binucleation and micronuclei and sveral types of inflammatory cell .Aims of current article was to investigate the histopathological observations and cytomorphological changes of epithelial cells component of oral mucosa present in direct attachment with orthodontic appliances via usage of exfoliated cytology technique. This study is designed to deal with 25 patients with orthodontic treatment in addition to 10 healthy persons as a control group to compare with them .Histological smears were obtained from oral mucosa of the healthy and treated groups along 3 - 6 months after the bingeing of orthodontic appliances traetment. Slides stained with giemsa dye and scrutinized by a light microscope. Many samples exhibited histopathological findings and cytomorphological changes which composed of many degrees of hypertrophy in mucosal epithelial cells, binucleation, micronuclei, perinuclear halos, and infiltration of inflammatory cells. In addition to that the epithelial cells of oral mucosa reveal cytomorphological alterations in patients who were wearing orthodontic appliances.